Modeling Patient-Specific Magnetic Drug Targeting Within the Intracranial Vasculature - Patronis, Alexander; Richardson, Robin A.; Schmieschek, Sebastian; Wylie, Brian J. N.; Nash, Rupert W.; Coveney, Peter V. (Frontiers in Physiology, 2018)
Drug targeting promises to substantially enhance future therapies, for example through the focussing of chemotherapeutic drugs at the site of a tumour, thus reducing the exposure of healthy tissue to unwanted damage. Promising work on the steering of medication in the human body employs magnetic fields acting on nanoparticles made of paramagnetic materials. We develop a computational tool to aid in the optimisation of the physical parameters of these particles and the magnetic configuration, estimating the fraction of particles reaching a given target site in a large patient-specific vascular system for different physiological states (heart rate, cardiac output, etc.). We demonstrate the excellent computational performance of our model by its application to the simulation of paramagnetic-nanoparticle-laden flows in a circle of Willis geometry obtained from an MRI scan. The results suggest a strong dependence of the particle density at the target site on the strength of the magnetic forcing and the local velocity of the background fluid flow.